Konflik Abad 11-12 M: Pertikaian Dinasti Mongol dengan Dinasti Khawarizm di Asia Tengah - Suci Indah Susanti; Yulianti Yulianti (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
The Mongol dynasty originated from the mainland region of Mongolia. With the leadership under Chengis Khan, the Mongols experienced greatness. The Mongol dynasty had experienced temporary trade relations with the Khawarizm dynasty. At that time, the Khawarizm dynasty was led by the sultan Al al-Din Muhammad Shah. The advancement of culture, especially in the field of weaponry of the Khawarizm dynasty, caused Chengis Khan to be amazed and interested in conducting trade relations with the Khawarizm dynasty. However, after Chengis Khan ordered the Mongol trade ambassadors to come to Khawarizm, Chengis Khan's envoys were massacred and killed. So that the purpose of compiling this article is to explain the conflict that occurred between the Mongol dynasty and the Khawarizm dynasty which had a considerable impact on Muslims. The method of preparing the articles used is literature study. The results and discussion include the causes of conflict between the Mongol dynasty and the Khawarizm dynasty, the attacks carried out by Chengis Khan against Khawarizm, the chronology of the conflict, and the impact of the conflict between the two dynasties.